HIGH INTENSITY INTERVAL TRAINING (HIIT) AS A MULTIDIMENSIONAL PERFORMANCE ENHANCER IN FITNESS (University Arena, 2025)
Background. High-Intensity Interval Training (HIIT) is an efficient exercise modality involving alternating short bouts of intense activity with recovery periods. It is increasingly popular among recreationally active individuals due to its time efficiency and broad health benefits. Literature supports its efficacy in enhancing cardiovascular capacity, promoting fat oxidation, and improving anaerobicperformance. Given rising sedentary trends among young adults, HIIT emerges as a practical alternative to traditional endurance training, especially for those with limited training time.Objectives. this study investigates the physiological impacts of a structured 6-week HIIT intervention on key fitness markers in recreationally active university students aged 20 to 25. The focus is on changes in maximal oxygen uptake (VO₂ Max), body fat percentage, and lower body muscular power, as reflected by vertical jump performance. By comparing pre- and post-intervention values, the aim is to evaluate HIIT’s benefits across aerobic capacity, body composition, and explosive strength.Methods. thirty recreationally active students (mean age: 22.1 ± 1.6 years) completed a 6-week HIIT program comprising three sessions per week. Each session included 20–25 minutes of high-intensity work intervals at 85–95% HRmax interspersed with active recovery. Assessments of VO₂ Max, vertical jump height, and body fat percentage were conducted before and after the program. Paired sample t-tests evaluated differences, repeated-measures ANOVA tested time effects, and Cohen’s d determinedthe magnitude of changes.Results. statistically significant improvements were observed across all outcome measures. VO₂ Max improved from 44.8 ± 4.7 to 49.9 ± 4.5 ml/kg/min (p < 0.001), vertical jump increased from 39.5 ± 3.2 to 43.1 ± 3.0 cm (p < 0.001), and body fat percentage decreased from 21.3 ± 2.9% to 18.1 ± 2.7% (p < 0.001). Large effect sizes confirmed the practical relevance of improvements.Conclusions. this study confirms that HIIT is a potent training modality for enhancing cardiovascular endurance, muscular power, and body composition in recreationally active young adults. Its time efficiency and multi-domain benefits support its integration into youth fitness and health programs.
Keywords: sports; HIIT; exercise; performance; fitness